Dissolved lead (Pb) concentrations and Pb isotope ratios along the East China Sea and Kuroshio transect—evidence for isopycnal transport and particle exchange - Chen, Mengli (2023)
Lead (Pb) isotopes are widely used in tracing processes that transport Pb within the environment due to the globally spread Pb pollution. In today’s ocean, Pb is mainly sourced from anthropogenic emissions and is removed by particle scavenging. However, recent efforts involving Pb isotopes have started to indicate that sediments at ocean boundary, either suspended or benthic, are a previously underestimated source and sink of Pb to the seawater dissolved pool. To assess the contributions of Pb from seawater-sediment boundary, we measured the dissolved Pb concentrations and isotopic compositions in seawater from the outer East China Sea (ECS) and along the Kuroshio. Along the Kuroshio, depth profiles exhibit highly similar Pb concentrations across constant density planes, suggesting isopycnal transport. Pb isotope ratios in most of the samples show strong contributions of aerosol Pb, except for seawaters from the ECS and deep Okinawa Trough (>800 m), which show evidences of crustal Pb contribution. The Okinawa Trough deep water has overlapping Pb isotope ratios with ECS water, where the suspended particulate matter is abundant. Our data on Pb isotopes in the ECS and the Okinawa Trough deep water, together with data from previous studies at other continental margins suggest that the seawater-sediment boundary along the continental shelves may be an important source and sink in marine Pb cycling.